2019
DOI: 10.1111/mec.15199
|View full text |Cite
|
Sign up to set email alerts
|

Chance and predictability in evolution: The genomic basis of convergent dietary specializations in an adaptive radiation

Abstract: The coexistence of multiple eco‐phenotypes in independently assembled communities makes island adaptive radiations the ideal framework to test convergence and parallelism in evolution. In the radiation of the spider genus Dysdera in the Canary Islands, species diversification occurs concomitant with repeated events of trophic specialization. These dietary shifts, to feed primarily on woodlice, are accompanied by modifications in morphology (mostly in the mouthparts), behaviour and nutritional physiology. To ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 102 publications
0
31
0
Order By: Relevance
“…During the assembly phase, we chose for each software the parameter values that generated the best assembly (Supplementary Table S1-7) in terms of (i) continuity and contig size statistics, such as the N50, L50, and the total number of sequences and bases assembled; and (ii) completeness measures, obtained as the fraction (and length) of a series of highly conserved proteins present in the draft genome. Particularly, we used 5 datasets, BUSCO v3 (BUSCO, RRID:SCR_015008) with genome option [40] using (i) the Arthropoda or (ii) the Metazoa dataset, (iii) the 457 core eukaryotic genes (CEGs) of Drosophila melanogaster [41], (iv) the 58,966 transcripts in the D. silvatica transcriptome [39], and (v) the 9,473 1:1 orthologs across 5 Dysdera species, D. silvatica; D. gomerensis Strand, 1911; D. verneaui Simon, 1883; D. tilosensis Wunderlich, 1992; and D. bandamae Schmidt, 1973 obtained from the comparative transcriptomics analysis of these species [42]. Finally, we performed an additional search to identify and remove possible contaminants in the generated scaffolds (Supplementary Table S1-7).…”
Section: De Novo Genome Assemblymentioning
confidence: 99%
“…During the assembly phase, we chose for each software the parameter values that generated the best assembly (Supplementary Table S1-7) in terms of (i) continuity and contig size statistics, such as the N50, L50, and the total number of sequences and bases assembled; and (ii) completeness measures, obtained as the fraction (and length) of a series of highly conserved proteins present in the draft genome. Particularly, we used 5 datasets, BUSCO v3 (BUSCO, RRID:SCR_015008) with genome option [40] using (i) the Arthropoda or (ii) the Metazoa dataset, (iii) the 457 core eukaryotic genes (CEGs) of Drosophila melanogaster [41], (iv) the 58,966 transcripts in the D. silvatica transcriptome [39], and (v) the 9,473 1:1 orthologs across 5 Dysdera species, D. silvatica; D. gomerensis Strand, 1911; D. verneaui Simon, 1883; D. tilosensis Wunderlich, 1992; and D. bandamae Schmidt, 1973 obtained from the comparative transcriptomics analysis of these species [42]. Finally, we performed an additional search to identify and remove possible contaminants in the generated scaffolds (Supplementary Table S1-7).…”
Section: De Novo Genome Assemblymentioning
confidence: 99%
“…Our model adjusts production efficiency in this case. Alternatively, a diet switch may not be desirable because the lower C:N prey item has traits that make it unpalatable or dangerous in large quantities (Pachl et al., 2012; Vizueta et al., 2019). In this case, limits on the diet composition need to be set manually.…”
Section: Resultsmentioning
confidence: 99%
“…A possible mechanism explaining their coexistence could be a shift in the trophic niche of P. stygia towards a more specialized diet. In several Dysdera species, elongation of chelicerae (Arnedo et al, 2007;Rezač et al, 2008) and shift in nutritional physiology (Toft & Macías-Hernández, 2017;Vizueta et al, 2019) have been shown to be critical adaptations for feeding on woodlice (Crustacea: Isopoda). Woodlice have evolved an array of morphological, chemical and behavioural defensive mechanisms that make them repulsive and unapproachable for many predatory arthropods (Gorvett, 1956).…”
Section: Stalita Pretneri Has the Largest Distribution Among The Threementioning
confidence: 99%